Comparing the Metcalf and Eddy and UCT steady state guidelines for sizing of biological nutrient removal activated sludge wastewater treatment plants - Murphy, Katelyn (Department of Civil Engineering, 2021)
This dissertation aims to provide both a qualitative and quantitative comparison of two steady state activated sludge (AS) design guidelines - the University of Cape Town (UCT) guideline used in South Africa and the Metcalf and Eddy (M&E) guideline used in North America and other parts of the world. It looks at the key similarities and differences between the two steady state AS design guidelines and how, under dynamic conditions, a system that is sized using a particular guideline (i) compares to its steady state results and (ii) performs under these dynamic conditions. In order to achieve the aims and objectives of this dissertation, an AS steady state model was created in a Microsoft Excel spreadsheet for the UCT guideline and M&E guideline respectively, and the models were analysed in terms of the key similarities and differences in the design guidelines in terms of inputs, equations, approaches and assumptions used. The results produced from each model were also analysed by setting the influent wastewater characteristics the same for each guideline and then analysing the results. The systems that were sized using the steady state AS models were then input into an AS system dynamic simulation software program, UCTOLD (which predicts virtually identical results as ASM1), together with a full set of diurnal influent data, to predict the behaviour of the system under steady state and dynamic conditions and compare the steady state predictions to those calculated in the steady state models and assess how the steady state model sized systems perform under dynamic loading conditions. The results of the analyses found that the two guidelines are similar in terms of organic material removal, nitrification and the sizing of the secondary settling tank, but differ significantly in the sizing of the anoxic reactor to achieve a certain nitrate removal. The key findings are: (1) Both UCT and M&E guidelines close the COD and N flux balances within 1%. (2) For organics removal only, at the same SRT, sludge production and oxygen demand are about 5% higher and lower respectively for the M&E guideline than the UCT guideline. When a UCT and M&E sized fully aerobic system is simulated with ASM1, this difference is repeated. The UCT guideline results are closely correlated with the ASM1 results but the M&E results deviate from those of ASM1. These differences arise because the M&E guideline assigns different values to the kinetic, stoichiometric and temperature sensitivity constants. If these constants in the M&E guideline are assigned the same values as the UCT guideline, virtually identical results are obtained. (3) For nitrification under fully aerobic conditions, the M&E guideline calculates a slightly shorter minimum aerobic SRT for nitrification than the UCT guideline. Again, the M&E guideline assigns different values to the nitrification kinetic (μAm20, bA20), stoichiometric (YA, Kn20) and temperature sensitivity constants (θμAm, θbA, θKn) than the UCT guideline. The M&E guideline calculates the minimum sludge age for nitrification, Rsm, using a fixed maximum specific growth rate of nitrifiers at 20oC (μAm20) at 0.90 g/(g.d), and after correcting for temperature, DO concentration in the aerobic reactor and assigning a safety factor (Sf = 1.5), the minimum sludge age for nitrification is slightly shorter than for the UCT guideline for a selected maximum specific growth rate of nitrifiers at 20oC (μAm20) of 0.45 g/(g.d) and assigning Sf = 1.25. In the M&E guideline the mass of nitrifiers is added to the reactor MLSS concentration which increases the MLSS mass in the reactor by about 1-3%. This is not done in the UCT guideline to maintain the COD balance for organics removal. At the same SRT in a fully aerobic system (i.e. aerobic SRT = system SRT), the oxygen demand for nitrification is closely similar in the two guidelines. This is because the calculated concentrations of nitrate produced by nitrification (called nitrification capacity Nc in the UCT guideline) are closely similar – the difference in the sludge production of the two guideline make little difference to the N taken up for sludge production. (4) If fully aerobic nitrifying reactors sized with the M&E and UCT guidelines are simulated with ASM1 at the same SRT, the same differences as with organic removal are observed. Hence the main difference in the sizing for nitrification in fully aerobic reactors in the two guidelines is the shorter aerobic SRT for nitrification in the M&E guideline (as a result of the different nitrification kinetics and safety factors) than in the UCT guideline. (5) Significant differences between the two guidelines emerge when adding an anoxic reactor for denitrification, such as for the anoxic aerobic nitrification - denitrification (ND) Modified Ludzack-Ettinger (MLE) system. This is because (5.1) the nitrifiers are assumed to behave differently under anoxic conditions in the two guidelines and (5.2) the effective specific denitrification rates of the OHO biomass in the anoxic reactor are much higher in the M&E guideline than in the UCT guideline. (6) With regard to difference (5.1), in the UCT guideline, the nitrifiers are assumed to grow only in the aerobic reactor but die in both the anoxic and aerobic reactors. In the M&E guideline, the nitrifiers are assumed to die (and grow) only in the aerobic reactor, i.e. they neither grow nor die in the anoxic reactor. Hence in the M&E guideline, the MLE system is sized based on an aerobic SRT, which excludes the mass of sludge in the anoxic reactor as in (3) above, but in the UCT guideline the MLE system is sized based on a system SRT, which includes the mass of sludge in the anoxic reactor. (7) With regard to difference (5.2), the faster specific denitrification rate determined with the M&E guideline yield much smaller anoxic reactors by at least 50% to achieve the same nitrate removal. (8) The consequence of these two differences is that the system SRT of the MLE system determined with the UCT guideline is considerably longer than that determined with the M&E guideline leading to larger anoxic, aerobic and system reactor volumes. This difference widens as the influent TKN/COD concentration ratio increases, i.e. as the concentration of nitrate to be denitrified increases. (9) When simulating the UCT sized MLE systems (under steady state conditions) with ASM1, very similar reactor MLVSS and MLSS concentration, effluent ammonia and nitrate concentrations and total oxygen demands are obtained with ASM1 and the UCT guideline. This indicates that the denitrification kinetics of the UCT guideline are well aligned with ASM1. This is not the case when simulating with ASM1 M&E guideline sized MLE systems under steady state conditions – while the effluent ammonia concentration compares well, the effluent nitrate concentration is far higher (increases from 6 mgNO3-N/l to above 20 mgNO3-N/l). This indicates that even though the denitrification kinetics of the M&E guideline were derived in part from ASM1 simulations, the denitrification kinetics of the M&E guideline are very poorly aligned with ASM1. (10) When the fmanx,M&E of the denitrification MLE system in (9) is increased to fmanx,UCT of 0.318 (but keeping the SRT = SRTsys,M&E) and simulated with ASM1, the effluent nitrate concentrations reduce from around 20 mgNO3-N/ℓ to around 6 mgNO3-N/ℓ, which is aligned with the UCT guideline ASM1 results. (11) The enhanced biological phosphorus removal (EBPR) parts of the UCT and M&E guidelines were not compared. While the EBPR part of the UCT guideline is complete and accounts for the phosphorus accumulating organisms (PAO) and their polyphosphorus content in the VSS and TSS calculations, as well as the differences in the denitrification kinetics in NDEBPR system compared with ND systems, which aligns the UCT NDEBPR guideline with ASM2, this is not the case in the M&E guideline. Because there is insufficient information in the M&E guideline to execute a complete NDEBPR system design calculation, the EBPR parts of the guidelines could not be compared. (12) The M&E overflow rates can be aligned with the UCT 1DFT to determine very similar SST surface areas. The lower resultant reactor MLSS of the M&E sized systems when simulated with ASM1 means that the SSTs will operate at a lower than designed for MLSS and thus under peak conditions (fq is 2.5 or greater) the SST will operate at a higher than permissible overflow rate. This is because the M&E SST sizing procedure does not include a 1DFT flux rating of 0.80 (as the UCT guideline does), which has the effect of increasing the SST surface area estimated by the 1DFT by 25%.